Heterogeneous ferroptosis susceptibility of macrophages caused by focal iron overload exacerbates rheumatoid arthritis - Yan Liu; Xiqing Luo; Ye Chen; Junlong Dang; Donglan Zeng; Xinghua Guo; Weizhen Weng; Jun Zhao; Xiaoyi Shi; Jingrong Chen; Bo Dong; Shuyuan Zhong; et al. (Redox Biology, 2024)
Focal iron overload is frequently observed in patients with rheumatoid arthritis (RA), yet its functional significance remains elusive. Herein, we report that iron deposition in lesion aggravates arthritis by inducing macrophage ferroptosis. We show that excessive iron in synovial fluid positively correlates with RA disease severity as does lipid hyperoxidation of focal monocyte/macrophages. Further study reveals high susceptibility to iron induced ferroptosis of the anti-inflammatory macrophages M2, while pro-inflammatory M1 are less affected. Distinct glutathione peroxidase 4 (GPX4) degradation depending on p62/SQSTM1 in the two cell types make great contribution mechanically. Of note, ferroptosis inhibitor liproxstatin-1 (LPX-1) can alleviate the progression of K/BxN serum-transfer induced arthritis (STIA) mice accompanied with increasing M2 macrophages proportion. We thus propose that the heterogeneous ferroptosis susceptibility of macrophage subtypes as well as consequent inflammation and immune disorders are potential biomarkers and therapeutic targets in RA.